Characteristics of extreme geoelectric fields and their possible causes: Localized peak enhancements. Issue 17 (8th September 2015) - Ngwira, Chigomezyo M.; Pulkkinen, Antti A.; Bernabeu, Emanuel; Eichner, Jan; Viljanen, Ari; Crowley, Geoff
Abstract One of the major challenges pertaining to extreme geomagnetic storms is to understand the basic processes associated with the development of dynamic magnetosphere‐ionosphere currents, which generate large induced surface geoelectric fields. Previous studies point out the existence of localized peak geoelectric field enhancements during extreme storms. We examined induced global geoelectric fields derived from ground‐based magnetometer recordings for 12 extreme geomagnetic storms between the years 1982 and 2005. For the present study two important extreme storms, 29 October 2003 and 13 March 1989, are shown. The primary purpose of this paper is to provide further evidence on the existence of localized peak geoelectric field enhancements and to show that the structure of the geoelectric field during these localized extremes at single sites can differ greatly from globally and regionally averaged fields. Although the physical processes that govern the development of these localized extremes are still not clear, we discuss some possible causes.